Chapter Supporting Informal Learning in Higher Education Internships - Melacarne, Claudio (Studies on Adult Learning and Education, 2018)
This paper addresses several critical issues relating to the organization of internships at universities, dealing above all with 'curricular' internships, i.e., those apprenticeship experiences included as mandatory in university courses. Starting from the idea of 'informal learning', the paper shows the strong connection between new workplace needs and the potentiality of pedagogical and reflective approaches in designing internship experiences